The school photography production of Ezequiel Fernández Santana 100 years later (1915-2015) - Soto Vázquez, José; Pérez Parejo, Ramón (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
Recent studies have revealed the interesting contributions of school photography to the research field History of Education. In this context, the photographs produced by Ezequiel Fernández Santana, taken between 1915 and 1938, constitute a milestone in the history of school photography in Spain. The original crystals were found in a landfill, so the had to be restored and digitized, according to contemporary criteria for documentary collections, as well as cataloged for their correct identification, chronology, and theme. Its current conservation will allow the study of school photography for artistic and propagandistic purposes, given that these materials account for a unique example in this regard. The corpus is an unpublished and exclusive material, not only because it comes from the same photographer, but also because of the amount (220 images), the conceptual unit, and the pedagogical perspective. In this sense, we have a work of double value, since the photographs were taken in media res by the teacher himself.